Does professional examination difficulty influence Bumiputra accounting students in Malaysian public universities to become professional accountants? - Nor Effa Dalilati Zulkafli; Khairun Nisa Mohd Arshad; Rozeta Che Omar; Sundari Subasini Nesamany (Asian Journal of Social Science Research, 2019)
The purpose of this paper is to investigate the relationship between professional examination difficulty and intention to become professional accountants among Bumiputra Accounting students in public universities in Malaysia. Quantitative survey method using a structured questionnaire was used to collect data, and the final-year Bumiputra accounting students at public universities and those who are undergoing the industrial training were selected as samples for the study. A total of 1,434 questionnaires was distributed and 388 were returned, giving a response rate of 27 percent. The findings revealed that there is no significant relationship between professional examination difficulty and intention to become professional accountants among the Bumiputra students in public Malaysia universities. The study concluded with a discussion of the theoretical and managerial implications as well as suggestions for future research.